Economic Structure and Services Efficiency of Turkish Beekeepers’ Association - Ceyhan, Vedat; Canan, Selime; Yıldırım, Çağatay; Türkten, Hatice (European Journal of Sustainable Development, 2017)
The study aimed to explore the current economic situation and services efficiency level of problems of beekeepers’ union and honey producers’ union in Turkey. Research data were collected from 73 beekeepers’ union and 58 honey producers’ union by using well-structured questionnaire. In the research, classical economic analysis approach was used to reveal socio-economic structure of unions. When measuring the efficiency, we followed two stage procedure. In first stage, data envelopment analysis was used, while Tobit model was used to explore the inefficiency determinants in second stage. Research results showed that typical Turkish beekeeper’s union obtained the ?1,59 from each expenditure by ?1. Economic condition of beekeeping unions was healthier than that of honey producers’ union. 11% of the Turkish beekeepers and honey producers’ unions were efficient, while the rest were inefficient. The most critical variables affected the efficiency level of unions were manager’s profile and the number of union member. Service efficiency level would increase, if the number of union member increased and profile of managers were improved. The research suggested that the typical Turkish beekeepers’ union would have 927 members to be efficient if they had no income sources without member fee. Keeping the basic record in the beekeepers’ association and developing information management system would accelerate the efficiency improving in Turkey. Keywords: beekeeping, beekeepers’ union, honey producers’ union, economic analysis, service efficiency